The Effect of Competence and Motivation on Performance: A Narrative Literature Review - Susanti, Desi; Amalia , Vyka Nur; Asbari, Masduki (International Journal of Social and Management Studies, 2023)
The purpose of writing this article is a narrative literature review of 3 (three) articles that discuss the effect of competence and motivation on employees’ performance, which aims to identify and summarize previously published articles without any criticism for the articles reviewed. The results of the review indicate that there is a significant influence between Competence and Motivation together on Employee Performance. The sampling technique uses saturated samples so that all members of the population are sampled in this study. The data collection technique used a questionnaire and the data analysis used was multiple regression analysis. The results showed that there was a positive and significant influence between competency and motivation variables on employee performance.